2007
DOI: 10.4161/cbt.6.4.4226
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitIon specifically sensitizes leukemic cells to anthracyclin-induced apoptosis through the accumulation of Bim and Bax pro-apoptotic proteins

Abstract: Proteasome inhibitors are a novel class of compounds that might increase sensitivity to chemotherapy for acute myeloid leukemia (AML). We quantified apoptosis in THP-1 cells incubated with idarubicin (IDA) alone or together with a low concentration of MG132 or bortezomib. The combination of both drugs yielded a percentage of apoptotic cells that was significantly higher than the additive effect of both drugs administered separately (p < 0.01). Isobologram analysis showed that both MG132 and bortezomib interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The results of the present study indicated that Bim may be important in bortezomib+daunorubicin-induced cell death. Consistent with this, several reports have shown that Bim-targeting contributes to the bortezomib-based combination regime (3335). However, whether Bim contributed to bortezomib+daunorubicin-induced mitochondria impairment, and how cotreatment with bortezomib and daunorubicin upregulated the expression of Bim required further investigation.…”
Section: Discussionsupporting
confidence: 70%
“…The results of the present study indicated that Bim may be important in bortezomib+daunorubicin-induced cell death. Consistent with this, several reports have shown that Bim-targeting contributes to the bortezomib-based combination regime (3335). However, whether Bim contributed to bortezomib+daunorubicin-induced mitochondria impairment, and how cotreatment with bortezomib and daunorubicin upregulated the expression of Bim required further investigation.…”
Section: Discussionsupporting
confidence: 70%
“…Acute myeloid leukaemia cells express higher levels of proteasomes compared with normal peripheral blood cells and are more sensitive to proteasome inhibition compared with normal haematopoietic cells [70,72,73]. Phase I trials have examined bortezomib monotherapy for paediatric acute leukaemia [74].…”
Section: Bortezomib In Leukaemiamentioning
confidence: 99%
“…The antitumor effect against leukemic cells of a combination of proteasome inhibitors with other drugs such as anthracyclin [34], arsenic trioxide [35] and more recently TRAIL itself has already been described by different authors. Particularly, Riccioni et al [27] showed that M4 and M5 AML display a high sensitivity to bortezomib-mediated apoptosis and this effect is increased when TRAIL is added.…”
Section: Discussionmentioning
confidence: 99%